Downregulation of c-Myc mediated ODC expression after purvalanol treatment is under control of upstream MAPK signaling axis in MCF-7 breast cancer cells - Alkurt, Gizem; Köse, Betsi; Çoker Gürkan, Ajda; Palavan Unsal, Narçin; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN; COŞKUN, DENİZ (Tubitak Scientific & Technical Research Council Turkey, Ataturk Bulvarı No 221, Kavaklıdere, Ankara, 00000, Turkey, 2014)
Roscovitine and purvalanol are specific cyclin-dependent kinase (CDK) inhibitors, which induce apoptosis by triggering cell cycle arrest in various cancer cells such as colon, prostate, and breast cancer cells. Although the apoptotic action of roscovitine was clarified at the molecular level, the exact mechanism of purvalanol-induced apoptosis is still under investigation. The mitogen-activated protein kinase (MAPK) signaling cascade is activated by different inducers related to growth, proliferation, differentiation processes, or environmental stress factors. Recent reports showed that modulation of MAPKs might lead to regulation of c-Myc, which is a transcription factor for the polyamine (PA) biosynthesis enzyme, ornithine decarboxylase (ODC). PAs are amine-derived cationic molecules that play crucial roles in cell proliferation, growth, and differentiation. In this study, we investigated the potential role of the MAPK signaling cascade in the purvalanol-induced apoptosis mechanism by comparing the results of roscovitine in MCF7 and MDA-MB-231 breast cancer cells. We found that CDK inhibitors decreased the cell viability in a dose-and time-dependent manner in MCF-7 and MDA-MB-231 cancer cells. Although both CDK inhibitors induced cell cycle arrest, which led to apoptosis by activating caspases and PARP cleavage in MCF-7 breast cancer cells, the apoptotic effect of purvalanol was less than that of roscovitine in MDA-MB-231 cells. Inhibition of MAPKs prevented CDK inhibitor-induced cell viability loss in both cell lines. We determined that purvalanol downregulated c-Myc and ODC expression levels, which led to sharp decrease in the PA pool in MCF-7 cells. On the contrary, purvalanol did not significantly alter c-Myc expression levels, which led to de novo biosynthesis of ODC in a time-dependent manner in MDA-MB-231 cells. Therefore, we suggest that a purvalanol-mediated resistance phenotype might be a possible outcome of c-Myc-mediated ODC expression level in MDA-MB-231 cells.
Keywords: Breast cancer; cyclin-dependent kinase inhibitors; purvalanol; mitogen-activated protein kinases; polyamines; apoptosis; c-Myc; Activated Protein-Kinase; Roscovitine-Induced Apoptosis; Polyamine Catabolic Pathway; Cyclin-Dependent Kinases; Cdk Inhibitors; Arrest; Death; Jnk; Erk; Growth